A model of community pharmacy-based services for type 2 diabetes patients in the Indonesian setting - Wibowo, Yosi Irawati (Curtin University, 2014)
This study analysed pharmacy-based services for type 2 diabetes patients in Surabaya, Indonesia, including: current practice, views on pharmacists’ roles, and factors influencing the practice development. Currently basic pharmacy services are provided but hampered by lack of pharmacist availability, remuneration, and other supporting resources (such as IT systems, appropriate training and standards/procedures). An Indonesian model of diabetes care in community pharmacies was developed for testing in the context of the new Indonesian health system.